ANALYZING HEARING-IMPAIRED STUDENTS' EXPERIENCES WITH INTERACTIVE AUDIO-VISUAL VIDEOS IN ENHANCING LISTENING COMPREHENSION - Rina Zakiah; Safithri Armin, Diah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Hearing-impaired students often encounter challenges in listening comprehension due to limited access to auditory information. Interactive audio-visual learning videos have the potential to support language learning by integrating visual and textual representations that facilitate comprehension. This study aimed to explore the experiences of hearing-impaired students in using interactive audio-visual learning videos to enhance listening comprehension. This study employed a qualitative case study approach involving two eighth-grade hearing-impaired students from a public special school in Medan, Indonesia. The participants were selected through purposive sampling. Data were collected through classroom observations, structured interviews, and documentation, and were analyzed using thematic analysis. The findings revealed three major themes: increased engagement and motivation, the important role of visual supports in facilitating comprehension, and challenges related to accessibility and information presentation. The participants reported that pictures, written text, and contextual visual information helped them understand English learning materials more effectively, while fast-paced content and hearing limitations remained challenges during the learning process. The findings provide insights into how interactive audio-visual learning videos support English listening instruction for hearing-impaired students and may inform teachers in designing more accessible and inclusive learning environments.